Determination of Median Tolerance Limit (LC50) of Clarias batrachus for Cadmium Chloride and Mercuric Chloride - Vincent2, J. Selvanathan1*, M. Suresh Kumar1, S. (Recent Research in Science and Technology, 2011)
Industries are the major sources of heavy metal pollution and it is released into water and soil. Heavy metals cause several ill effects to aquatic living organisms and environment. The acute toxicity of chosen metals (Cadmium and Mercury) against fresh water Clarias batrachus (Cat fish) and the chronic toxicity of sublethal concentrations of heavy metals on the different organs such as liver, gill, muscle, kidney and brain of the chosen fresh water fish. Adult cat fish treated separately with Cadmium Chloride (CdCl2) and Mercury Chloride (HgCl2) for 24, 48, 72, and 96hr at different dose levels showed significant behavioral changes in the Lethal concentration were determined by probit analysis method. The LC 50 values for CdCl2, HgCl2 were found as 8.21ppm, 1.85ppm; respectively. Among the toxicants selected, HgCl2 is more toxic than CdCl2 in cat fish.